2015
DOI: 10.1016/j.jbiomech.2015.02.041
|View full text |Cite|
|
Sign up to set email alerts
|

A multi-compartment 3-D finite element model of rectocele and its interaction with cystocele

Abstract: We developed a subject-specific 3-D finite element model to understand the mechanics underlying formation of female pelvic organ prolapse, specifically a rectocele and its interaction with a cystocele. The model was created from MRI 3-D geometry of a healthy 45 year-old multiparous woman. It included anterior and posterior vaginal walls, levator ani muscle, cardinal and uterosacral ligaments, anterior and posterior arcus tendineus fascia pelvis, arcus tendineus levator ani, perineal body, perineal membrane and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…Tie constraints in ABAQUS that binds two shared surfaces were used to couple motions of parts which are biologically connected (e.g., the coccygeus muscle and the coccyx) and to model the connecting effects of fasciae (e.g., the tendineous arch of levator ani muscle between the iliococcygeus muscle and the obturator internus muscle). Connector elements, with the ability to model connective tissues such ligaments [12], were employed in this study to model the uterosacral and cardinal ligaments. The Abaqus/Explicit solver was used for finite element method implementation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tie constraints in ABAQUS that binds two shared surfaces were used to couple motions of parts which are biologically connected (e.g., the coccygeus muscle and the coccyx) and to model the connecting effects of fasciae (e.g., the tendineous arch of levator ani muscle between the iliococcygeus muscle and the obturator internus muscle). Connector elements, with the ability to model connective tissues such ligaments [12], were employed in this study to model the uterosacral and cardinal ligaments. The Abaqus/Explicit solver was used for finite element method implementation.…”
Section: Methodsmentioning
confidence: 99%
“…Computer simulation using the finite element method (FEM) has been proven to be a useful tool due to its ability to conveniently simulate various impairment conditions and keep these comparisons based on the same subject, computer simulation using finite element method (FEM) has been proven a useful tool [11]. Several computer models developed from MR images have been reported recently in studies of female pelvic floor dysfunctions such as pelvic organ prolapse [12,13], childbirth related levator ani muscle damages [14,15] and ligament impairment [16]. However, the clinical application of these models and their comparisons to the true dynamic response of the pelvis is limited due to either 1) missing or simplified important anatomical structures (e.g., the bladder, rectum, vaginal canal, uterus are not included [14,15]; buffering fatty tissues are not included [1216]) or 2) less accurate realization of boundary conditions (e.g., direct inferior displacement is applied on the uterus [13]; intra-abdominal pressure is directly applied on the muscle [16] or vaginal wall [12] that are studied).…”
Section: Introductionmentioning
confidence: 99%
“…Levator ani muscle impairment caused a larger urogenital hiatus size, longer length of the distal vagina exposed to a pressure differential, larger apical descent, and resulted in a larger cystocele size. Interactions between the anterior and posterior compartments have also been demonstrated 8 that help explain postoperative development of new prolapse in the opposite compartment, despite its support appearing normal prior to the operation. 9 …”
Section: How Do the Pelvic Floor Structures Work Together In Preventimentioning
confidence: 99%
“…Tie constraints that bind two shared surfaces were used to couple motions of parts which are biologically connected and to model the connecting effects of fasciae (e.g., the tendinous arch of levator ani muscle). Connector elements, with the ability to model connective tissues, such as ligaments [17], were employed in this study to model the ligaments surrounding the urethra (e.g., the pubourethral ligament). Although soft tissues show viscoelastic behavior [23,24], a previous study found quasi-linear material property of urological soft tissues when the stress level is under 70% of the maximal stress value [25].…”
Section: Methodsmentioning
confidence: 99%
“…Computational models, based on realistic female pelvic anatomy, offer a useful tool for quantitative biomechanical analysis to female pelvic floor dysfunctions [14]. Models have been employed to study pelvic organ prolapse [15][16][17], childbirth-related trauma [18,19], and ligament impairment [20]. However, these models often missed some necessary anatomical structures that maintain the integrity of the natural pelvic anatomy, and efforts have been rarely made to study the interventional treatments.…”
Section: Introductionmentioning
confidence: 99%